Representasi Nilai Keluarga dalam Film Gara-Gara Warisan (Analisis Semiotika Roland Barthes) - Widha Azhari, Aglista; Wirawanda, Yudha (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Film is a mass communication medium that functions to entertain, films can also display important values which sometimes have great potential to influence audiences. The aim of this research is to find out the family values contained in the film Gara - Gara Pahlawan. This research uses Stuart Hall’s representation theory which aims to discover and see how family values are contained in the film. The second theory used is Roland Barthes’ semiotic theory, this theory is used to carry out an analysis that uses the meaning of denotation, connotation and myth to find symbols, meanings and messages of family values contained in the film. The method used to conduct research is a qualitative analysis method. The results of this research found that there is a meaning of family values that is in accordance with the meaning of family values based on reality in society and it is hoped that this research will be able to show that the function of family values can be a function of love, a socio-cultural function, an economic function, and a protection function.